1981
DOI: 10.1152/jappl.1981.50.4.869
|View full text |Cite
|
Sign up to set email alerts
|

Direct and reflex bronchoconstriction induced by histamine aerosol inhalation in dogs

Abstract: Histamine aerosols were administered to nine anesthetized, paralyzed, mechanically ventilated mongrel dogs with the cervical vagi first intact, then sectioned, and then peripherally stimulated at two intensities. Pulmonary resistance (RL) was measured, and dose-response curves were constructed in the four conditions. All dogs had dose-related increases in RL with increasing histamine aerosol concentrations. After the vagi were cut, the degree to which constant levels of vagal stimulation altered the dose-respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The effect of a second inhaled spasmogen may thus be potentiated by histamine pre-treatment because the second spasmogen will have easier access to the ASM. In regard to the nerves, many studies have shown synergistic interactions between spasmogens and electrical stimulation of the vagal nerves (17,33,57,88,114,137,217,258). Similarly, a decrease in responsiveness to spasmogens (other than ACh (88)) was observed following vagotomy (59,137,157,258), cooling of the vagal nerves (58,88), or treatments with either atropine (59,219), tetrodotoxin (219) or hexamethonium (59).…”
Section: Interactive Synergisms Between Spasmogensmentioning
confidence: 99%
“…The effect of a second inhaled spasmogen may thus be potentiated by histamine pre-treatment because the second spasmogen will have easier access to the ASM. In regard to the nerves, many studies have shown synergistic interactions between spasmogens and electrical stimulation of the vagal nerves (17,33,57,88,114,137,217,258). Similarly, a decrease in responsiveness to spasmogens (other than ACh (88)) was observed following vagotomy (59,137,157,258), cooling of the vagal nerves (58,88), or treatments with either atropine (59,219), tetrodotoxin (219) or hexamethonium (59).…”
Section: Interactive Synergisms Between Spasmogensmentioning
confidence: 99%